The CADRE Project: Looking at the Development of Beginning Teachers - Sheryl McGlamery; Jarene Fluckinger; Nancy Edick (Educational Considerations, 2006)
The CADRE Project is a collaborative teacher induction effort between higher education and K-12 practitioners. The Metropolitan Omaha Educational Consortium (MOEC), comprised of seven metropolitan Omaha public school districts and the University of Nebraska at Omaha College of Education, coordinates this project. This project is a true collaborative effort involving public school superintendents, university administrators, and faculty and staff from both entities.